2016
DOI: 10.3390/cryst6050056
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between Crystallography Data and Theoretical Parameters and the Formation of Intramolecular Hydrogen Bonds: Benznidazole

Abstract: Abstract:The conformational preferences of benznidazole were examined through the application of DFT, PCM and QTAIM calculations, whose results were compared with crystallography data. The geometries were fully optimized with minimum potential energy surface by means of the Relaxed Potential Energy Surface Scan (RPESS) at AM1, followed by the B3LYP/6-311++G(d,p) theoretical level. As a result, the s-cis conformation (1C) was shown to be more stable (4.78 kcal¨mol´1) than s-trans (1T). The Quantum Theory Atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The experimental benznidazole structure was determined by using X-ray diffraction by Soares-Sobrinho et al while their new polymorphs structures were elucidated by Honorato et al by using the same technique (Soares-Sobrinho, et al, 2008;Honorato, et al, 2014). Previously, the theoretical structures of benznidazole were studied by Tonin et al and, recently, two conformations were reported for this species by Oliveira et al in order to investigate the intra-molecular hydrogen bonds in their structures (Tonin, et al, 2009;Olivera, et al, 2016). These authors have optimized two structures of benznidazole in aqueous solution which are the s-cis and s-trans forms by using the B3LYP/6-311++G(d,p) method and the PCM model (Olivera, et al, 2016).…”
Section: Suggested Citationmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental benznidazole structure was determined by using X-ray diffraction by Soares-Sobrinho et al while their new polymorphs structures were elucidated by Honorato et al by using the same technique (Soares-Sobrinho, et al, 2008;Honorato, et al, 2014). Previously, the theoretical structures of benznidazole were studied by Tonin et al and, recently, two conformations were reported for this species by Oliveira et al in order to investigate the intra-molecular hydrogen bonds in their structures (Tonin, et al, 2009;Olivera, et al, 2016). These authors have optimized two structures of benznidazole in aqueous solution which are the s-cis and s-trans forms by using the B3LYP/6-311++G(d,p) method and the PCM model (Olivera, et al, 2016).…”
Section: Suggested Citationmentioning
confidence: 99%
“…Previously, the theoretical structures of benznidazole were studied by Tonin et al and, recently, two conformations were reported for this species by Oliveira et al in order to investigate the intra-molecular hydrogen bonds in their structures (Tonin, et al, 2009;Olivera, et al, 2016). These authors have optimized two structures of benznidazole in aqueous solution which are the s-cis and s-trans forms by using the B3LYP/6-311++G(d,p) method and the PCM model (Olivera, et al, 2016). Those two conformations can be seen in Figure 1.…”
Section: Suggested Citationmentioning
confidence: 99%
See 1 more Smart Citation